English grammar for dummies ebook - Woods, Geraldine (Dummies., 2011)
The fun and easy way to improve your grammar Enhancing your speaking and writing skills helps in everyday situations, such as writing a paper for school, giving a presentation to a company's bigwigs, or communicating effectively with family and friends. English Grammar For Dummies , 2nd Edition gives you the latest techniques for improving your efficiency with English grammar and punctuation. Teaches the rules of verbs, adjectives, and adverbs; prepositions, propositions, and pronoun pronouncements; punctuation; possessives; and proofreading skills for all communication Geraldine Woods is the author of English Grammar Workbook For Dummies, College Admission Essays For Dummies, Research Papers For Dummies, SAT I For Dummies, 6th Edition, AP English Literature For Dummies, and AP English Language For Dummies For speakers and writers of all skill levels, English Grammar For Dummies , 2nd Edition provides easy-to-follow, practical information for improving your command of English grammar.